Dakwah Bil Hikmah dalam Eksplorasi Komparatif Intervensi Spiritual Keagamaan untuk Menopang Kesehatan Mental Pasien Kemoterapi - Hakim, Hari Rahman; Nurjanah, Titin; Latifah, Siti Lutfi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
Cancer remains a persistent global health challenge, often accompanied by profound emotional and spiritual distress, particularly during intensive treatment phases such as chemotherapy. This study presents an in-depth analysis of the effectiveness of various forms of spiritual interventions, including individual spiritual counseling, spiritual support groups, and religious meditation or dzikir practices, in sustaining the psychological well-being of patients. Employing a qualitative research design with a phenomenological approach, this study explores the subjective experiences of patients undergoing these interventions. The theoretical framework is grounded in Kenneth I. Pargament’s theory of religious coping, which emphasizes faith and religious practices as adaptive mechanisms in confronting life’s adversities. The findings of this study are expected to offer contextual and applicable insights into the role of spirituality in enhancing mental resilience among cancer patients, and to generate practical recommendations for healthcare providers on integrating spiritual dimensions into a holistic care system.